Barriers in the Educational Attainment of Tribal Girl students in Salem District of Tamil Nadu State, India. - Maanhvizhi Emayavaramban; Ramesh Kumar Kandasamy; Selvam Muthusamy; Manivannan Manickam (Faculty of Teacher Training and Education, Universitas Terbuka, 2020)
The objective of this study is to identify the barriers prevailing among the tribal girl students in the attainment of their education. A qualitative study was conducted in 7 hill ranges of Salem district, Tamil Nadu, India with a semi-structured interview schedule. A total of 21 small group discussion for female tribal students (n=50), teachers working in tribal areas (n=31), and parents of tribal girl students (n=18). It was found that lack of public transport, poor staff pattern, unavailability of basic infrastructure facilities like road, the curriculum that does not provide support for their poor economic conditions, with very little scope for vocational education formed barrier for educational attainment. It is concluded that providing proper public transport, vocational education, stable and sufficient staff, due care by the parents, availability of nearby schools, would raise educational attainment.Ã‚Â